1999
DOI: 10.1136/jnnp.67.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of refractory temporal lobe epilepsy on cognitive abilities: a cross sectional study

Abstract: Objective-Intractable epilepsy is related to various transient and chronic brain electric and neurochemical disturbances. There is increasing evidence that chronic epilepsy induces secondary neuronal metabolic and structural decline. However, there is no convincing evidence that the cognitive abilities of patients deteriorate with increasing duration of intractable epilepsy. A second ANOVA including education as factor showed that in patients with higher educational attainment, the mean FSIQ was stable for a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
161
1
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(181 citation statements)
references
References 47 publications
13
161
1
6
Order By: Relevance
“…Although this was observed in the majority of cases, it is not the only possible route of spread. The functional and structural changes in the mesial temporal regions correlate with seizure frequency (33,36,37). The most likely explanation for the reduced metabolism in remote brain areas is a functional inhibition of the remote regions by ongoing, subclinical epileptic activity in the epileptogenic mesial temporal lobe (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although this was observed in the majority of cases, it is not the only possible route of spread. The functional and structural changes in the mesial temporal regions correlate with seizure frequency (33,36,37). The most likely explanation for the reduced metabolism in remote brain areas is a functional inhibition of the remote regions by ongoing, subclinical epileptic activity in the epileptogenic mesial temporal lobe (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is less clear that surgery could improve the neuropsychological or psychiatric morbidity associated with refractory epilepsy (77,78). For example, adults are at risk of verbal memory impairment after removal of the dominant temporal lobe (78,79).…”
Section: Can "Progressive Epilepsy" Be Halted?mentioning
confidence: 99%
“…The present investigators studied exclusively a group of patients with GTCS not associated with brain damage or other factors which could produce cognitive impairment. The other investigators explained that the cognitive impairment could be attributed to brain damage, age of onset of epilepsy, nature and location of seizure focus, duration of epilepsy, anticonvulsant drugs and epilepsy related surgery 5,6,7,8 Few earlier studies reported that there is significant cognitive impairment in patients with idiopathic GTCS without brain damage. 10,11 The cognitive impairment could be due to subtle brain damage which the present investigators could not exclude with neurological and neuropsychological investigations.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several variables have been implicated in the development of cognitive deficits, including age at onset, nature of seizures, location of seizure foci, duration of seizure free period, use of antiepileptic drugs and epilepsy related surgery. 5,6,7,8 Other studies have focused on cognitive performance at disease onset and found that individuals with epilepsy performed worse than siblings or normal controls on several neuropsychological tests. 9,10,11,12 The domains of cognition most often affected include attention and concentration, language, memory, intelligence, executive functions, motor speed and visuo-spatial processing speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation